Assessing the adoption and impact of climate-smart agricultural practices on smallholder maize farmers’ livelihoods in Sub-Saharan Africa: a systematic review - Minentle L. Mnukwa; Lelethu Mdoda; Maxwell Mudhara (Frontiers in Sustainable Food Systems)
Climate change threatens agricultural sustainability in Sub-Saharan Africa (SSA), where rain-fed farming supports millions of livelihoods. While climate-smart agriculture (CSA) offers potential solutions, comprehensive evidence synthesis regarding its adoption patterns and impacts among smallholder maize farmers remains limited. This systematic review analysed 50 peer-reviewed studies (2003–2023) using a three-stage screening process across EBSCOhost, Scopus, and Web of Science databases. The Mixed Methods Appraisal Tool (MMAT) was employed for quality assessment of the selected studies. Regional variations in CSA adoption rates were observed (Eastern Africa 56.7%, Southern Africa 43.2%, Western Africa 38.9%), influenced by institutional and socioeconomic factors. Extension services increased adoption 2.8 times, while secure land tenure improved long-term investment by 60%. Gender disparities were evident, with female farmers showing 40–55% adoption rates compared to male farmers’ 55–70%. Economic constraints significantly impacted adoption, with high initial costs reducing uptake by 65% among resource-poor farmers, while credit access improved adoption by 45%. Critical research gaps include insufficient long-term impact studies beyond 2–3 years and inadequate analysis of gender-specific constraints. Future research should prioritize developing standardized methodologies for ecosystem service valuation, examining indigenous knowledge integration, and conducting comprehensive longitudinal studies on sustained adoption patterns. Policy recommendations emphasise integrated approaches combining institutional support, innovative financing mechanisms, and enhanced market linkages, with particular attention to gender-responsive interventions addressing multiple adoption barriers simultaneously.